Bladder cancer and occupational exposure: estimating the workers potentially at risk in Italy - Alberto Scarselli; Patrizia Scano; Alessandro Marinaccio; Sergio Iavicoli (Istituto Superiore di Sanità, 2011)
Bladder cancer is one of the most common occupational tumours. The objective of this study is to evaluate the number of workers potentially at risk in Italy. Economic activities entailing bladder cancer risk were selected on the basis of the excesses resulting from studies reporting risk estimates. Firms and the number of workers potentially at risk were retrieved from the National Institute for Occupational Safety and Prevention (ISPESL) database of enterprises. Excluding low level exposures, the number of workers (blue-collars) likely exposed to bladder cancer risk in the industry and services is 366 175 ± 11 096 (248 573 ± 7 533 men, and 117 603 ± 3564 women). The North-Western area of Italy shows the majority of workers potentially at risk (86 625 ± 2625 men, and 27 225 ± 725 women). Quantify the number of exposed workers is the first step for performing analyses on occupational cancer risks. National database of enterprises may be useful in identifying potential risk situations for worker's health.